The vine basket - La Valley, Josanne (Houghton Mifflin Harcourt, 2013)
Life has been hard for fourteen-year-old Mehrigul, a member of the Uyghur tribal group scorned by the Chinese communist regime, so when an American offers to buy all the baskets she can make in three weeks, Mehrigul strives for a better future for herself and her family despite her father's opposition.